Deslocamentos patrimoniais: polifonias, memórias e visualidades em rio de contas (BA) - Silva, Jean Pierre Pierote (2014)
This dissertation is a study based on representations, practices and current senses of heritage in Rio de Contas (BA). The use of artistic interventions as a way of illustrating the ethnography, as well as the questioning of the place of speech of the researcher in the context of the nearby alterity, are some of the reflections presented in this thesis. I will also describe and interpret the speeches of the speakers of this research, using these tools as a theoretical and methodological strategy to overcome and move itself the speeches referring to the senses of heritage in the city of Rio de Contas. Categories such as Backlands (Sertão), memory, stigma, and social representation will also be analyzed. Thus, the narrative built here also propose to question the experiences lived by my ethnographic encounter, verifying the extent to which the relationship between the landscape, visual and memory representations relate to the heritages representations shared by the social actors participants in the frame of this ethnographic field in context.